Optimization of Class Provision In The Implementation of Moving Class Using The Simplex Method - Virotun Nisaul Fadia; Ida Fitriana Ambarsari; Zainul Munawwir (Universitas Wiralodra, 2026)
Allocation of class provision in the implementation of moving classes is an important thing that needs to be considered to obtain optimal learning. The problem of optimizing class provision is still an obstacle to most problems in the field of education. One of them occurred in the implementation of moving classes at SMAN 1 Panji, which provided classes based on students' interests and talents. The curriculum deputy has difficulty determining the number of classes provided according to the subjects that students are interested in, to obtain optimal class provision. This study aims to solve the problem of optimizing class provision in the implementation of moving classes for grade 11 at SMAN 1 Panji with the right allocation of student interests in order to obtain optimal results. The method used is a descriptive qualitative method with a case study. Data collection methods include field studies (observation and interviews) and literature reviews. Meanwhile, data analysis uses the simplex method and MATLAB software. Data analysis techniques using observation and interviews. Meanwhile, based on the optimization results, the recommended class solution for the implementation of moving class for grade 11 at SMAN 1 Panji is 24 IPA (Natural Sciences) classes and 16 IPS (Social Sciences) classes. On the other hand, 0 Mathematics and Informatics classes (not required to be provided). Furthermore, by using MATLAB software, the same results are obtained as using the simplex method, but with a simple, effective, and efficient algorithm, of course, with precise results, and the use of this software aims to avoid calculation errors.